Pleomorphic dermal sarcoma: Clinicopathological features and outcomes from a 5‐year tertiary referral centre experience. Issue 11 (11th November 2021) - Logan, Ian T.; Vroobel, Katherine M.; le Grange, Franel; Perrett, Conal M.
Abstract: Background: Pleomorphic dermal sarcoma (PDS) describes rare dermal‐based malignant tumours that are morphologically similar to atypical fibroxanthoma (AFX). PDS may be differentiated from AFX by the presence of one or more of the following histologic features: subcutaneous invasion, tumour necrosis, lymphovascular invasion (LVI), and/or perineural infiltration (PNI). Aims: To further define the clinicopathological features, surgical management, and outcomes of PDS primary tumours. Methods and Results: This study was a retrospective observational case series using a database search from 2012 to 2017. Inclusion criteria required all cases to meet the histopathologic criteria for PDS as confirmed by a specialist soft‐tissue histopathologist. A total of n  = 17 cases were included with a median age of 78 years (range 66–85). All tumours were located on the head and neck, with 13/17 located on the scalp. Primary treatment was with wide local excision (WLE) in all cases. Median follow‐up was 48 months. Local recurrence occurred in 4/17 cases (24%) and distant metastasis in 2/17 cases (12%). Conclusion: PDS behaves more aggressively than atypical fibroxanthoma with which it shares a biologic continuum. The optimal surgical management approach is yet to be determined.